2015
DOI: 10.1016/j.neures.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

BDNF promoter I methylation correlates between post-mortem human peripheral and brain tissues

Abstract: a b s t r a c tSeveral psychiatric disorders have been associated with CpG methylation changes in CG rich promoters of the brain-derived neurotrophic factor (BDNF) mainly by extracting DNA from peripheral blood cells. Whether changes in peripheral DNA methylation can be used as a proxy for brain-specific alterations remains an open question. In this study we aimed to compare DNA methylation levels in BDNF promoter regions in human blood cells, muscle and brain regions using bisulfite-pyrosequencing. We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 36 publications
2
50
0
1
Order By: Relevance
“…Therefore, exon VI seemed a promising candidate region to study in the available peripheral blood specimen. Notably, findings published after data collection for the present study suggest that DNA methylation of BDNF exon I as measured in the periphery could be used to estimate DNA methylation of the same gene regions in the brain (Stenz et al, 2015), making BDNF exon I another interesting candidate region. Sixth, the sample was derived from an ad-hoc student sample and might not be representative of the general population.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, exon VI seemed a promising candidate region to study in the available peripheral blood specimen. Notably, findings published after data collection for the present study suggest that DNA methylation of BDNF exon I as measured in the periphery could be used to estimate DNA methylation of the same gene regions in the brain (Stenz et al, 2015), making BDNF exon I another interesting candidate region. Sixth, the sample was derived from an ad-hoc student sample and might not be representative of the general population.…”
Section: Discussionmentioning
confidence: 70%
“…However, at least for COMT and BDNF , there are some hints for (strong) correlations between methylation variations in peripheral and brain tissue 40, 41 but more research is needed before the associations found in our current study can be integrated into functional pathways from genes, environment and epigenetic processes towards brain functions and mental disorders.…”
Section: Discussionmentioning
confidence: 83%
“…Weaver et al, 2004; Roth et al, 2009; Miller et al, 2010). Some studies have suggested that one tissue may be a good proxy for another (Houde et al, 2014; Iyer et al, 2010; Liberman et al, 2012; Stenz et al, 2014). The present study highlights a crucial distinction between tissue concordance of patterns of methylation across a region of the genome (very high in these samples) and the ability to use individual variation in methylation in one tissue to make inferences about another (not supported in this study).…”
Section: Discussionmentioning
confidence: 99%